ANALISIS MANAJEMEN PERBANKAN SYARIAH SISTEM PENGAWASAN BERBASIS DIGITAL BJB SYARIAH KCP BOGOR JEMBATAN MERAH - Prasetya, Bagas Dwi; Thantawi, Tubagus Rifqy; Rizal, Muhammad (Jurnal Penelitian Perbankan Syariah: Program Studi Perbankan Syariah., 2024)
Sharia banking supervision from a normative juridical perspective. The administration and supervision of sharia banking, which is based on Law Number 3 of 2004 which amends Law Number 23 of 1999 concerning Bank Indonesia and Law No. 21 of 2008, is the authority of Bank Indonesia (BI). After the enactment of Law No. 21 of 2011 concerning the Financial Services Authority (OJK), supervision of sharia banking which was previously the responsibility of BI was transferred to the OJK. Therefore, the sharia banking regulatory and development institution also shifted from BI to OJK, which included the Sharia Banking Committee (KPS), which was later changed and expanded by OJK to become the Sharia Financial Services Development Committee (KPJKS). For this reason, good coordination cooperation between BI and OJK is needed. However, supervision from a sharia perspective is still carried out by the National Sharia Council-Indonesian Ulema Council (DSN-MUI), and at the sharia financial institution (LKS) level, the Sharia Supervisory Board (DPS) acts as an extension of DSN-MUI. This is because the fatwas issued by DSN-MUI remain in effect, and the regulations issued by BI, both in the form of Bank Indonesia Regulations (PBI) and Bank Indonesia Circular Letters (SEBI), remain the legal basis for supervision of Islamic banks by DPS.